2001
DOI: 10.1243/0957650011539027
|View full text |Cite
|
Sign up to set email alerts
|

Non-axisymmetric turbine end wall profiling

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…The vortex was not significantly weakened, but its migration across the passage towards the suction surface was partially blocked. Similar research on end wall profiling was carried out by Gregory-Smith et al [4] , Ingram et al [5,6] . Weiss and Fottner [7] have done experiments on the influence of load distribution on secondary flows in a straight turbine cascade.…”
Section: Introductionmentioning
confidence: 53%
“…The vortex was not significantly weakened, but its migration across the passage towards the suction surface was partially blocked. Similar research on end wall profiling was carried out by Gregory-Smith et al [4] , Ingram et al [5,6] . Weiss and Fottner [7] have done experiments on the influence of load distribution on secondary flows in a straight turbine cascade.…”
Section: Introductionmentioning
confidence: 53%
“…Usually the fillet (and the endwall) is truncated at the front and rear of the endwall to save space and the endwall is designed with streamlined elements transitioned into the fillet, e.g. with a nonaxisymmetric endwall contouring [8]. To address this problem we reconstruct the fillet curve C F as a clear and significant feature for the base part of the blade.…”
Section: Slicing Surfaces For the Base Partmentioning
confidence: 99%
“…The resulting secondary flows were significantly reduced in the whole passage and the measured net secondary loss was reduced by 30%. With the same design method, Gregory-Smith et al 12 redesigned the Durham cascade nonaxisymmetric endwall to restrict the profile in the blade passage so that the nonaxisymmetric endwall design was suitable for application to a real machine. The test results indicated that the new profile showed a similar reduction in the strength of the secondary flow but did not produce the same level of loss reduction as the old one designed by Harvey et al 10 With the refined measurement technique, which captured the flow near the endwall more accurately in the cascade, Ingram et al 13 presented some new results of the Durham cascade with the nonaxisymmetric endwall profile [10][11][12] to investigate their flow mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…With the same design method, Gregory-Smith et al 12 redesigned the Durham cascade nonaxisymmetric endwall to restrict the profile in the blade passage so that the nonaxisymmetric endwall design was suitable for application to a real machine. The test results indicated that the new profile showed a similar reduction in the strength of the secondary flow but did not produce the same level of loss reduction as the old one designed by Harvey et al 10 With the refined measurement technique, which captured the flow near the endwall more accurately in the cascade, Ingram et al 13 presented some new results of the Durham cascade with the nonaxisymmetric endwall profile [10][11][12] to investigate their flow mechanism. In contrast to the work of Gregory-Smith, the measurement results showed that the design of Gregory-Smith had more reduction in secondary loss because the measurements capture the undesirable corner vortex in the design of Harvey et al 10 Praisner et al 14 designed the nonaxisymmetric endwall profiles for three different LP turbine blades.…”
Section: Introductionmentioning
confidence: 99%